1997
DOI: 10.1108/01443579710175556
|View full text |Cite
|
Sign up to set email alerts
|

An internal customer service quality data envelopment analysis model for bank branches

Abstract: Over the last few years data envelopment analysis (DEA) has been gaining increasing popularity as a performance assessment methodology. DEA has been successfully applied to bank branch performance evaluation. However, most DEA models which have been developed for bank branch performance assessment do not include service quality as an output. Service quality has been considered by many as the key to gaining competitive advantage and customer loyalty. Develops a DEA model that can be used to provide direction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 24 publications
1
67
0
3
Order By: Relevance
“…2. Soteriou and Stavrinides (2000)  Analysis of internal service quality through data envelopment analysis (DAE)  Optimum utilization of inputs such as consumable resources and work volume and its transformation into output -service quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2. Soteriou and Stavrinides (2000)  Analysis of internal service quality through data envelopment analysis (DAE)  Optimum utilization of inputs such as consumable resources and work volume and its transformation into output -service quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ren [16] indicated that DEA was a novel and feasible method for finding efficient bioethanol production scenarios. According to Soteriou [17], DEA was an effective model for bank branch performance assessment in terms of internal customer service quality. The main purpose of this research was to measure the operating efficiency of sustainable industrial logistics.…”
Section: Related Research About Deamentioning
confidence: 99%
“…Average MAPE (%) DMUs Average MAPE (%) DMU 1 0.9462 DMU 11 1.4125 DMU 2 0.7709 DMU 12 1.227 DMU 3 0.27 DMU 13 0.6516 DMU 4 1.2972 DMU 14 2.742 DMU 5 1.983 DMU 15 0.384 DMU 6 0.505 DMU 16 0.469 DMU 7 1.263 DMU 17 1.083 DMU 8 1.4853 DMU 18 1.65 DMU 9 2.662 DMU 19 0.588 DMU 10 3.0697…”
Section: Dmusmentioning
confidence: 99%
“…(cf. Parasuraman et al, 1988;Brogowicz et al, 1990;Cronin & Taylor, 1994;Berkley & Gupta, 1994;Spreng & Mackoy, 1996;Philip & Hazlett, 1997;Sweeney et al, 1997;Oh, 1999;Dabholkar et al, 2000;Frost & Kumar, 2000;Soteriou & Stavrinides, 2000;Broderick & Vachirapornpuk, 2002;Grönroos, 1984Grönroos, , 2000Zhu et al, 2002;Santos, 2003;Vijayvargy, 2014). Some examples of these models developed by these researchers are: the information technology (IT) alignment model, the service quality and satisfaction model, PCP (Pivotal, Core, Peripheral) attribute model, the retail service quality and perceived value model, the customer value and customer satisfaction model , the antecedents and mediator model, the internal service quality model, the internal service quality data envelope analysis model, the service quality model for internet banking, the service quality model for IT-related business, and the model of e-service quality.…”
Section: Introductionmentioning
confidence: 99%